{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Math 3

# Math 3 - Section 2.4 Linear Equations 1 Compare y’ = —y...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 2.4. Linear Equations 1. Compare y’ = —y + 2 with y’ = a(t)y + f(t) and note that a(t) = -—1. Consequently, an integrating factor is found with efldt_ r 140‘) = f_“m‘i’: = e . Multiply both sides of our equation by this integrat— ing factor and check that the left-hand side of the resulting equation is the derivative of a product. e'(y’ + y) = 2e‘ (e’y)’ = 28‘ Integrate and solve for y. e’ y = 2e‘ + C y(t) = 2 + C e“’ We have a(t) = 3, so u(t) = e"3’ . Multiplying we see that the equation becomes 3—3:), I __=3e—3:y 5e‘3‘. We verify that the left-hand side is the (hi-'2‘ (2—3‘ y, so when we integrate we get 5 e-3'yo) = ~3e—3‘ + C. Solving for y, we get y(t) = —§ + Ce3'. Compare y’ + (2/x)y = (cosx)/Jt2 w'ﬁ f = a(x)x + f(x) and note that a(x) = —2/.r_ CI.- sequently, an integrating factor is found will —=.IxI’z’ Multiply both sides of our equation by the ﬁll“ factor and note that the left-hand side of the m “()0 = ef—a(x)dx = efZ/xdx = e21n|.r|_ 6. If we write the equations as x’ = (4/!)x + t3, we see that a(t) = 4/t. Thus the integrating factor is “0) = e—f(4/t)dt = e—4lnr : [—4. Multiplying by u, the equation becomes t’4x’ — 41‘5x = 1"]. After verifying that the left~hand side is the deriva- tive of t‘4x, we can integrate and get z-4x(t) =1nt + C. Hence the general solution is x(t) = t4lnr + Cr“. 14. Compare y’ = y + he“ with y’ = a(x)y + f(x) andnote thata(x) = 1. Consequently, an integrating factor is found with “(/0 = ef ‘a(x)dx ____ ef—l dx = 8—1. Multiply both sides of our equation by the integrating factor and note that the left-hand side of the resulting equation is the derivative of a product. e_‘y' — e'xy 2 22:6" (e‘xyy = 2xe" Integration by parts yields foe" dx = 2.766" — f 26x = 2xe‘ — ge‘ + C. Consequently, e“)! = 2256" — 29" + C y(x) = 2xe2" — 2.22" + cex The initial condition provides 3 = y(0) = 2(0)e2(°) — 2e2<0> + Ceo = —2 + C. Consequently, C = 5 and y(x) 2 he” —2e2x+56". ...
View Full Document

{[ snackBarMessage ]}

### Page1 / 3

Math 3 - Section 2.4 Linear Equations 1 Compare y’ = —y...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online